2008
DOI: 10.1007/s10823-008-9079-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Older Chinese Men and Women from Hong Kong in the Impact of Urinary Incontinence on their Lives

Abstract: This study reports the epidemiology of urinary incontinence (UI) and its impact on the social lives of older Chinese people in Hong Kong, a modern city in China. It also examines the relationship between sex and this impact, as well as the extent of UI in a convenience sample of 101 sufferers aged 60 or older. This study was cross-sectional and used face-to-face interviews with a structured questionnaire. A number of findings concur with studies conducted in Western countries. Prevalence of UI increased with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Compared with the male–other group, married older men might be more likely to feel shameful about incontinence, as their spouse might find out and have to deal with it, and thus experience a decline in social participation. This finding supported previous evidence that a sex difference exists in the impact of UI on social participation, and further detected a marital status difference …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared with the male–other group, married older men might be more likely to feel shameful about incontinence, as their spouse might find out and have to deal with it, and thus experience a decline in social participation. This finding supported previous evidence that a sex difference exists in the impact of UI on social participation, and further detected a marital status difference …”
Section: Discussionsupporting
confidence: 91%
“…UI can restrict patients’ participation in social activities . Because of frequent urination, and feelings of humiliation and embarrassment, incontinent patients tend to avoid social gatherings, visiting friends, travel and participation in other social activities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riss and Kargl (2011) found a connection between UI and QoL identifying three problematic areas: daily life, recreational activities, and sex life. In addition, research has shown a decrease in social participation (Lee, 2009), physical health (Mishra et al, 2009), emotional health (Miu et al, 2010), and lower scores on QoL measures (Aguilar-Navarro et al, 2012;Cheater et al, 2008;DuBeau et al, 1998DuBeau et al, , 2006Dugan et al, 1998;Hawkins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Having a UI may have several adverse effects on a person’s social life (Hayder and Schnepp, 2010; Lee, 2009; Miu et al, 2010) since women limit social activities due to the possible shame and fear associated with leaving the house (Hayder and Schnepp, 2010; Miu et al, 2010). Hagglund and Wadensten (2007) found altered sexual relationships and a need for distancing in the women’s narratives.…”
Section: Introductionmentioning
confidence: 99%